2014
DOI: 10.5732/cjc.013.10108
|View full text |Cite
|
Sign up to set email alerts
|

The role of EPH receptors in cancer-related epithelial-mesenchymal transition

Abstract: Erythropoietin-producing hepatoma (EPH) receptors are considered the largest family of receptor tyrosine kinases and play key roles in physiological and pathologic processes in development and disease. EPH receptors are often overexpressed in human malignancies and are associated with poor prognosis. However, the functions of EPH receptors in epithelial-mesenchymal transition (EMT) remain largely unknown. This review depicts the relationship between EPH receptors and the EMT marker E-cadherin as well as the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 97 publications
0
22
0
Order By: Relevance
“…Eph receptors induce EMT through oncogenic signaling pathways such as Wnt, Ras/MAPK, Akt-mTOR, and Notch. 43 We also observed that the Src/FAK signaling is involved in the EphB4/ephrin-B2-induced EMT process. Perturbation of ephrin-B2 reverses the EMT phenotype by E-cadherin downregulation and hence makes mutant p53-expressing cancer cells more susceptible to chemotherapeutics.…”
Section: Discussionmentioning
confidence: 67%
“…Eph receptors induce EMT through oncogenic signaling pathways such as Wnt, Ras/MAPK, Akt-mTOR, and Notch. 43 We also observed that the Src/FAK signaling is involved in the EphB4/ephrin-B2-induced EMT process. Perturbation of ephrin-B2 reverses the EMT phenotype by E-cadherin downregulation and hence makes mutant p53-expressing cancer cells more susceptible to chemotherapeutics.…”
Section: Discussionmentioning
confidence: 67%
“…EPH receptor A3 ( EPHA3 ) was found to have the highest negative fold change in the microarray. EPH receptors have been shown to be involved in the EMT pathway, and may regulate E-cadherin and Snail expression, as well as regulate MMP-2 activity [3235]. Three different annexins were the highest upregulated genes when SSX was knocked down, and annexins have been shown to attenuate EMT in breast cancer [36] and regulate TGF-beta signaling [37].…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Metastatic cancer cells typically undergo morphological changes that result in decreased intercellular adhesion and increased cell motility, a process defined as the EMT. [8][9][10] A variety of cytokines, including chemokines, inflammatory factors, and growth factors, and tumor-infiltrating bone marrow-derived components, including macrophages and related cell types, are involved in tumor invasion and metastasis. 11,12 However, the involvement of inflammatory cells in cancer cell metastasis remains controversial.…”
Section: Cox-2 Promotes Metastasis In Nasopharyngeal Carcinoma By Medmentioning
confidence: 99%